Integrasi manajemen strategi, inovasi, dan transformasi digital dalam meningkatkan daya saing perusahaan - Ahla, Hilwiyatul (Maliki Interdisciplinary Journal, 2025)
Strategic management plays a crucial role in guiding companies to achieve sustainable competitive advantage amidst the dynamics of the global business environment. This article aims to deeply analyze the role of management strategy in enhancing corporate competitiveness through a resource-based approach (RBA), innovation, and digital transformation. This study utilizes a literature review method from five relevant national and international journals. The synthesis results indicate that management strategy functions not only as a planning tool but also as an adaptive system capable of balancing internal strengths and external opportunities. Effective implementation strategies include environmental analysis, innovative policy formulation, digital technology implementation, and continuous performance evaluation. In the context of small and medium enterprises (SMEs), strategies based on local innovation and cross-sector collaboration have been shown to improve regional competitiveness and economic performance. In conclusion, the success of management strategy depends on the organization’s ability to integrate innovation, human resources, and technology to create a competitive advantage that is resilient to global change.